Marine Biodiversity of Areas beyond National Jurisdiction - Nordquist, Myron H.; Long, Ronán (Center for Oceans Law and Policy, 2021)
Marine Biodiversity of Areas beyond National Jurisdiction (BBNJ) identifies the major issues at stake in the BBNJ negotiations and examines the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction. This timely volume offers cutting edge contributions from leading global experts on access and benefit sharing of marine genetic resources; environmental impact assessments; capacity building and transfer of technology as well as Arctic environmental issues including security and shipping. Cross-cutting themes including the potential impact on existing legal frameworks and instruments are also explored. Readership: All those interested in current issues related to the Law of the Sea.